Genome-resolved tracking of Penicillium commune in a bakery facility highlights long-term environmental persistence - Fagerlund, Annette; Kummen, Charlotte; Åsli, Anette Wold; Finne, Cathrine Kure (Frontiers in Fungal Biology, 2025)
Mould spoilage is a major challenge in bakery production, yet the sources and persistence of contaminating strains remain poorly understood. We applied whole-genome sequencing (WGS) to 68 isolates from potato-cereal wraps and their production environment in a Norwegian bakery. Barcode-based identification using ITS, BenA, CaM, and RPB2 confirmed that 65 isolates belonged to the Penicillium commune/Penicillium fuscoglaucum lineage but could not fully resolve species status or resolve strain-level differences. Genome-wide comparison using Mash placed these isolates in a single clade within series Camembertiorum, distinct from cheese-associated taxa. SNP analysis revealed extremely low diversity within the main cluster (up to 60 SNPs after recombination filtering) and demonstrated that genetically similar strains persisted in the facility for 15 months, spanning multiple products and environmental samples. No consistent association with potato suppliers or production dates was detected, indicating that long-term environmental reservoirs were the main source of contamination. These findings show that persistent clonal lineages can survive routine cleaning in dry bakery environments, enabling recurrent contamination. WGS provided the strain-level resolution needed to uncover this persistence and clarify phylogenetic placement, underscoring its value for monitoring and controlling mould spoilage in food production.